SCHOLAR IN THE SPECTACLE OF PARAMETRIZATION – BETWEEN AUTHENTICITY AND GAME OF APPEARANCES - Cybal-Michalska, Agnieszka (Rocznik Pedagogiczny, 2018)
By referring to the metaphor of the theater – the theater of the reality of parametrization in which we the people of science participate – the author is wondering whether the servitude towards science can be identified with scientometrics, i.e., parametrization in the form that is known to us, where at least two of the indicators are subjective, namely: the type of the criteria and their weight. In the article, the emphasis is placed on the theatrical space of construction of the relation of “co-presence” which is not free from our need for recognition, individuality, uniqueness and being the best, at the top of the ranking of parametrization, “skillfully” playing our role of the “scientist” on the stage, which connects but also divides because of that, i.e. the place occupied on that stage. The acts are the spaces of our scientific activity, which – by capturing the “difference” in relation to others and the “difference” in relation to ourselves in time – allow us to be, to crystallize our image, to further define ourselves and to be recognizable in the role of a scientist in a reality that was not chosen by us, but is implemented according to codified rules of the game.